Adopting Supply Chain Financial Solutions for the Risk Associated with Supply Chain Financial Flows - Gunawan, Hero; Nurfarina, Anne; Amaliawiati, Lia; Alaeddin, Omar (ExcelingTech, 2019)
The main aim behind this empirical research is to investigate the impact of the adoption of the supply chain financial solutions on the supply chain financial flows of manufacturing firms listed in Indonesian Stock Exchange. In addition to that the study has also investigated the moderating role of cash conversion cycle in the relationship between supply chain financial solutions and supply chain financial flows. To achieve the objective of the study we have employed the panel data method and have used the linear repression and hierarchical regression techniques. The final sample comprise of 756 firm year observations over the period of 6 years from 2012-2017.teh findings of the study have shown an agreement with the proposed findings of the study. The cash conversion cycle appears as strong moderator. In author knowledge this is among few pioneering studies on this issue and will be helpful for future policy makings.